Different Parameters Affecting to Rhodomyrtus tomentosa Wine Fermentation - N. P. Minh (Journal of Global Pharma Technology, 2016)
Fermentation is a relatively efficient, low energy preservation process which increases the shelf life, and decreases the need for refrigeration or other forms of food preservation technology. It is, therefore, a highly appropriate technique for use in developing countries and remote areas where access to sophisticated equipment is limited. Rhodomyrtus tomentosa plays an important holistic role in the daily lives of several ancient cultures, providing medicinal benefits. There is limited study mentioning to processing of this nutritional fruit. Therefore we explored a wine fermentation from Rhodomyrtus tomentosa by focusing on the effect of different parameters such as pectinase concentration and time of treatment for juice extraction, yeast inculate for wine fermentation, fermentation temperature and secondary fermentation to wine quality. Our results proved that 2.5% pectinase was used for juice extraction in 40 minutes, 2.5% sacchromyces cerevisiae was used for the main fermentation at 29.5oC in 15 days, and 6 weeks of aging in dark bottle at 10.5oC was enough to get a pleasant Rhodomyrtus tomentosa quality. Using Rhodomyrtus tomentosa having medicinal and nutritional value as a substrate for wine production, the health benefits of them can be improved widely.Keywords: Rhodomyrtus tomentosa, Wine, Pectinase, Fermentation, Sacchromyces cerevisiae, Aging.